Evolution of integrated management systems research on the Journal of Cleaner Production: Identification of contributions and gaps in the literature - Nunhes, Thais Vieira [UNESP] (2016)
Certifiable management systems, such as ISO 9001 Quality Management System (QMS), ISO 14001 Environmental Management System (EMS) and OHSAS 18001 Occupational Health and Safety Management System (OHSMS), have gained popularity within different countries around the world. The integration of these management systems (MS) that work in a separated way has been pointed out by many researchers as a way to improve the overall management system efficiency. In this context, it is remarkable the engagement of the Journal of Cleaner Production (JCP) in contributing to developing the Integrated Management System (IMS) field. The objective of the present study is to analyze the evolution of IMS research on JCP, presenting its contributions and gaps in the IMS scope. The analysis was conducted through a theoretical framework of IMS on JCP. The identified contributions were split into five groups: (I) IMS and Sustainability, (II) IMS and Strategy, Performance and Innovation, (III) Analysis of integration levels and motivations, benefits and difficulties of IMS implementation, (IV) IMS methods, guidelines and maturity model and (V) IMS and Corporate Social Responsibility. The results showed the JCP is the most influential journal in IMS area. Regarding the gaps in the IMS literature, we found lack of studies approaching IMS and performance (mainly environmental performance), IMS and sustainability, methods and guidelines for IMS based on empirical evidences, analysis of the levels of integration and motivations, benefits and difficulties taking into account the implementation strategy adopted, IMS and innovation management and IMS and social responsibility. It is suggested the gaps found in this paper are explored in future studies.